Intropostface to Lockdown Theory - Panayotov, Stanimir (Identities: Journal for Politics, Gender and Culture, 2020)
Author(s): Stanimir Panayotov Title (English): Intropostface to Lockdown Theory Journal Reference: Identities: Journal for Politics, Gender and Culture Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 8 Page Count: 1 Citation (English): Stanimir Panayotov, “Intropostface to Lockdown Theory,” Identities: Journal for Politics, Gender and Culture, Vol. 17, No. 1 (Summer 2020): 8.